Mental Insanity Assessment of Pedophilia: The Importance of the Trans-Disciplinary Approach. Reflections on Two Cases - Scarpazza, Cristina; Pennati, Ambrogio; Sartori, Giuseppe (Frontiers in Neuroscience, 2018)
A 60 plus-year-old male was charged with pedophilia for forcing a child to touch him inappropriately near a primary school fence. In another case, a 70 plus-year-old male was charged with pedophilia for intimately touching a boy in a cinema. What led them to manifest this socially-inappropriate and legally-relevant behavior? Is there an explanation for the sexually-related behavioral changes emerging late in life of these two men? Indeed, a common point exists between the two men: both were found to suffer from highly-disabling neurological conditions, known to have a potential effect on social behavior. Specifically, a large right frontoparietal meningioma was found to have important influence on the first man's cognition and control inhibition, whereas frontotemporal dementia prevented the second man from understanding the moral disvalue of his sexually-inappropriate behavior and controlling his sexual impulses. In the current presentation, particular emphasis is placed on the logical reasoning supporting the conclusions that both the pedophiles should be considered not guilty by reason of insanity. Furthermore, experimental methods have been used to explore both cases, which rely on the existence of cognitive models for the phenomena under study, the integration of insights offered by different disciplines and the application of a variety of tools and approaches that follow the “convergence of evidence” principle, which could be safely used in court to support a mental insanity claim. Here, we describe how the use of the experimental method could become useful to reduce the uncertainty in mental insanity assessments. The use of a transdisciplinary, scientifically-grounded approach can help to change the way legal phenomena are interpreted. For instance, when assessing mental insanity, consultants should not only investigate the eventual existence of a diagnosis, but should assess the cognitive/affective abilities that are necessary to understand our own behavior and emotions as well as those of others. The criteria for responsibility should be symptoms-based and not diagnosis-based. Since pedophilia is among the most hideous behaviors condemned by society, a more comprehensive and transdisciplinary approach is recommended in court.